2020
DOI: 10.21203/rs.3.rs-86217/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expression Profile of Micrornas (106b-3p, 130b-3, 145-3p and 199a-5p) in Urine and Serum Samples From Patients With the Diagnosis of Bladder Cancer

Abstract: Background MicroRNAs (miRNA) are short, single stranded, non-coding RNAs that play an important role in controlling gene expression at the post-transcriptional stage. There is no bladder cancer marker that has been approved as an alternative for diagnostic cystoscopy and urine cytology so far, thus research for alternative, more sensitive, and less invasive methods of bladder cancer detection are being made. The aim of the study was to compare the relative expression levels of miRNAs in patients with bladder c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Zaravinos et al, (2012) have reported downregulation of miR-145 in BC tissue samples compared with neighboring normal urothelium and their results were supported by Avgeris et al, (2015) who aimed to evaluate the unexplored clinical potential of the urological cancer-related miR-145 in a total of 279 bladder tissue specimens were included in their study (133 BC, 107 adjacent normal and 39 healthy samples), they stated that the expression level of miR-145 was significantly decreased. Kutwin et al, (2021) collected urine and serum samples from patients with bladder cancer, they assessed the expression of 4 miRNAs (106b-3p, 130b-3, 145 and 199a-5p) using real-time PCR, the statistical analysis was performed with the Mann-Whitney U test which revealed that miRNA-145 was significantly under-expressed in urine (P=0.0111) compared with control group, whereas in serum, they did not find relevant differences between groups (P=0.0903).…”
Section: Discussionmentioning
confidence: 99%
“…Zaravinos et al, (2012) have reported downregulation of miR-145 in BC tissue samples compared with neighboring normal urothelium and their results were supported by Avgeris et al, (2015) who aimed to evaluate the unexplored clinical potential of the urological cancer-related miR-145 in a total of 279 bladder tissue specimens were included in their study (133 BC, 107 adjacent normal and 39 healthy samples), they stated that the expression level of miR-145 was significantly decreased. Kutwin et al, (2021) collected urine and serum samples from patients with bladder cancer, they assessed the expression of 4 miRNAs (106b-3p, 130b-3, 145 and 199a-5p) using real-time PCR, the statistical analysis was performed with the Mann-Whitney U test which revealed that miRNA-145 was significantly under-expressed in urine (P=0.0111) compared with control group, whereas in serum, they did not find relevant differences between groups (P=0.0903).…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA screening based on serum is a convenient and widely applicable diagnostic method, especially noninvasive. A lot of studies have explored if the serum miRNAs serve as the diagnostic tool in BC ( 19 , 20 ). In our study, we paid more attention to BC detection and designed a three-stage study to evaluate the diagnostic performance of serum miRNAs in BC.…”
Section: Discussionmentioning
confidence: 99%